nalysis of the West African Monsoon onset mechanism: Regional dynamics or large scale forcing? - (:unkn) unknown (My University, 2010)
The rainy season in West Africa is crucial for local population. The onset of the monsoon (WAM) occurs in late June and corresponds to the weakening of convection over the entire region and to the sudden transition of rainfall from the Guinean coast to the Sahel. The mechanism which provokes this monsoon "jump" is investigated in this thesis through modeling experiments. The ability of the regional WRF model to reproduce the movement of MAO in 2006 was first evaluated. Different parameterizations of convection and boundary layer have been tested, providing an analysis of their impact on the simulations. Sensitivity tests were then performed in order to evaluate the role of the Saharan heat low and SST (mechanisms proposed in other studies) to provoke the WAM onset. The results show that the transitional phase depends on large scale dynamics rather than on regional climate. More specifically, the Indian monsoon onset releases a westward propagating Rossby wave which passes over north Africa favoring dry air intrusion over west Africa inhibiting convection. In parallel, the meridional gradient of surface pressure is strengthened, accelerating the WAM and therefor enhancing humidity advection over the Sahel. Once the wave is passed, convective activity gets reorganized above the Sahel where thermodynamic conditions are more favorable. The use of simulations by the LMDz global model confirmed the role of the Indian monsoon over the period 1989-2008, however with years more or less marked.
Keywords: African Research